SCHFI 6.2 Self-Care Confidence Scale - Brazilian version: psychometric analysis using the Rasch model - Diná de Almeida Lopes Monteiro da Cruz; Ana Maria Miranda Martins Wilson; Michele Nakahara Melo; Ana Paula da Conceição; Leidy Johanna Rueda Diaz (Universidade de São Paulo, 2020)
Objective: to evaluate the psychometric properties of the Self-Care Confidence Scale in heart failure in the Brazilian version of the Self Care Heart Failure Index, version 6.2, using the Rasch model criteria. Method: secondary study, of psychometric analysis, using the Rasch model, of the six items of the scale. The sample consisted of 409 patients with heart failure undergoing outpatient treatment [mean age 57.9 (standard deviation = 11.6) years, 54.8% male]. Results: of the total of six items, one ("De maneira geral, você está confiante sobre estar livre dos sintomas de insuficiência cardíaca?") presented maladjustment to the model (Infit = 1.84 and Outfit = 1.99). After the exclusion of this item, the others showed a good fit, composed one dimension and explained 55% of the variance in the data; the categories of response to the items were adequate, the values of separation and reliability of person were 2.13 and 0.82, respectively, and Cronbach's alpha was 0.87. Items of extreme difficulty were identified and there is no differential functioning of the items in relation to sex. Conclusion: with the exclusion of the first item, the Self-Care Confidence Scale showed good psychometric properties, with caution in interpreting the results of the six-item scale.